PENGARUH STORE ATMOSPHERE DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI HARMONI SQUARE GRAND MERCURE JAKARTA HARMONI - Ashley, Felicia; Kurniawan Yuwono, Victor; Grasielda, Ivana; Soediro, Moses (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to examine the effect of store atmosphere (X1) and service quality (X2) on customer loyalty (Y) through customer satisfaction (Z) as an intervening variable at Harmoni Square Grand Mercure Jakarta Harmoni. A purposive sampling method was used to distribute a 4-Likert scale questionnaire to 152 customers of Harmoni Square Grand Mercure Jakarta Harmoni online via Google Form and in person. The structural equation model based on Partial Least Squares (PLS-SEM) was used to identify characteristics that have a significant impact on customer loyalty at Harmoni Square Grand Mercure Jakarta Harmoni. The questionnaire consists of two parts: the first part includes respondent identity data such as name, gender, age, and occupation, while the second part includes research variables such as store atmosphere, service quality, customer satisfaction, and customer loyalty. The data analysis results indicate that there is a significant effect and positive value between the store atmosphere and customer satisfaction, service quality and customer loyalty, service quality and customer satisfaction, and customer satisfaction and customer loyalty. However, the store atmosphere and customer loyalty variables have a less significant effect. Furthermore, this study also shows that customer satisfaction partially mediates the relationship between store atmosphere and service quality towards customer loyalty.